PERANCANGAN SISTEM PELAPORAN KEUANGAN SMK NEGERI 1 KECAMATAN LUAK BERBASIS JARINGAN - Febby Apri Wenando; Dony Novaliendry; Ahmaddul Hadi (Universitas Negeri Padang, 2014)
Schoolasan organization needsasystemtosupport all activitiesboth academicorschoolmanagement. Fields of school management system are management of curriculum, studentmanagement, personnel management, financialmanagementandpreventivemanagement ofschool facilities and infrastructure. Financial managementisthe managementactions/financialadministration, including record keeping, payroll, implementation, accountabilityandreporting. Design payroll report system forSMANegeri 1X Koto Diatasuseful to support thesmooth running ofthe services thatthe payrollreportsystemwillbe betterorganizedinterms ofexpenditureandincome. Thissystem designusingMySQLfor Databaseand programming languagePHP.Design system of payrollSMANegeri 1X Koto Diatasimplementedtofacilitate theadministrative officerand theparties involved in thepayrollreport ofschool. In theservice ofprocessorreportwill befaster and more accuratebecause thecalculationis done automatically. Keywords: Systems, Payroll Report, Payroll Systems, SchoolsPayroll